2020
DOI: 10.1016/j.ijid.2020.09.1422
|View full text |Cite
|
Sign up to set email alerts
|

Co-production of MCR-1 and NDM-1 by Escherichia coli sequence type 31 isolated from a newborn in Moscow, Russia

Abstract: An Escherichia coli sequence type 31 isolate co-harbouring mcr-1 and bla NDM-1 genes on the plasmids of Incl2 and IncC groups, respectively, was recovered from a newborn with ventilator-associated pneumonia in Moscow, Russia. The convergence of polymyxin and carbapenem resistance and its expansion beyond Southeast Asia is a serious threat to human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
4
0
3
Order By: Relevance
“…In this study, the prevalence of phenotypic colistin resistance and of the mobile colistin resistance ( mcr- 1) genes among clinical E. coli and K. pneumoniae isolates collected from hospitalized patients in Russia in 2013–2018 as part of sentinel surveillance was systematically assessed, and in-depth analysis of the genome sequences of mcr -bearing isolates and plasmids was performed. While there have been several reports of mcr-1 positive isolates recovered from human and animal sources in Russia [ 12 , 13 , 14 , 15 ], to our knowledge, this study is the first to report the prevalence and genomic context of mcr-1 in clinical isolates collected from geographically distant sites across Russia.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, the prevalence of phenotypic colistin resistance and of the mobile colistin resistance ( mcr- 1) genes among clinical E. coli and K. pneumoniae isolates collected from hospitalized patients in Russia in 2013–2018 as part of sentinel surveillance was systematically assessed, and in-depth analysis of the genome sequences of mcr -bearing isolates and plasmids was performed. While there have been several reports of mcr-1 positive isolates recovered from human and animal sources in Russia [ 12 , 13 , 14 , 15 ], to our knowledge, this study is the first to report the prevalence and genomic context of mcr-1 in clinical isolates collected from geographically distant sites across Russia.…”
Section: Discussionmentioning
confidence: 91%
“…Several research groups have previously reported on the sporadic occurrence of mcr-1 in Russia and described the corresponding mcr -bearing plasmids [ 12 , 13 , 14 , 15 ]. In this study, we aimed to systematically assess the prevalence of colistin resistance and of mcr genes in clinical Escherichia coli and Klebsiella pneumoniae isolates from Russian sentinel surveillance and to determine phenotypic and genomic characteristics of mcr -carrying isolates and plasmids.…”
Section: Introductionmentioning
confidence: 99%
“…Даже изоляты Eco-49 и Есо-84, выделенные в одном стационаре и содержащие идентичные плазмиды IncX4, относились к разным сиквенс-типам [42]. Для штаммов, выделенных от пациентов, был характерен несколько более высокий уровень ассоциированной резистентности к антибиотикам разных групп, так пять из семи изолятов проявляли устойчивость к цефалоспоринам III поколения, несли гены бета-лактамаз расширенного спектра группы СТХ-М и/или бета-лактамаз класса С. Особый интерес представляет, выделенный в г. Грозный у новорождённого ребенка с пороком сердца, изолят Eco-5571, у которого были одновременно выявлены гены mcr-1 и bla NDM-1 [43]. При этом ген mcr-1 был локализован на плазмиде практически идентичной плазмиде, выдев 2018 г. на Алтае от дикой птицы Чёрный коршун (Milvus migrans) [44].…”
Section: Discussionunclassified
“…Подавляющее число плазмид обладают конъюгативной активностью. Доминирующими и наиболее распространёнными группами плазмид являются IncHI2, IncI2, и IncX4, при этом плазмиды демонстрируют высокий уровень консервативности, а также отсутствие выраженных доминирующих генетических линий бактерий, с которыми бы эти типы плазмид ассоциировались [32,33].…”
Section: горизонтальный перенос генов Mcr-1unclassified
“…Описан изолят E.coli от новорожденного, находящегося в реанимации, демонстрирующий ко-продукцию mcr-1 и карбапенемазы NDM-1. Плазмида, несущая ген mcr-1, оказалась гомологичной плазмиде, описанной у изолята от чёрного коршуна [57].…”
Section: описания в россииunclassified